Silver(I)-selective electrodes based on rare earth element double-decker porphyrins - Joon, Narender Kumar (2021)
Various double-decker porphyrins accommodating rare earth elements (Sm, Tb, Y) were investigated as ionophores in potentiometric ion sensors. The studied ion-selective electrodes based on double-decker porphyrins were primarily selective to Ag ions. The experimentally derived selectivity coefficients were compared to theoretical predictions based on density functional theory (DFT) calculations of the metal-binding energies (ΔE) of double-decker porphyrin-metal ion complexes. Although DFT calculations were performed in vacuo, without taking into account ion-solvent and ion-membrane interactions, this computational approach showed relatively good correlation with the experimentally observed selectivity patterns of the ion-selective electrodes. Thus, DFT calculations were found to be a useful predictive tool when designing new ionophores for ion-selective electrodes.